2005
DOI: 10.1002/jclp.20204
|View full text |Cite
|
Sign up to set email alerts
|

Brief scheduled phone support from a clinician to enhance computer‐aided self‐help for obsessive‐compulsive disorder: Randomized controlled trial

Abstract: Treatment-resistant obsessive-compulsive disorder (OCD) patients from around the United Kingdom who employed computer-guided self-help by using BTSteps over 17 weeks were randomized to have brief live phone support from a clinician either (1) in nine Scheduled clinician-initiated calls or (2) only in calls Requested by the patient (n=22 per condition). Call content and mean duration were similar across conditions. Scheduled-support patients dropped out significantly less often, did more homework of self-exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
117
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(124 citation statements)
references
References 12 publications
4
117
3
Order By: Relevance
“…An additional program, OCFighter, is described in detail in Box 4. 32,33,41 In addition, Box 5 outlines the successful rollout by the Australian government of a nationwide Internet-delivered CBT program. 24 ).…”
Section: What Resources Are Available For Internet-delivered Cbt?mentioning
confidence: 99%
See 1 more Smart Citation
“…An additional program, OCFighter, is described in detail in Box 4. 32,33,41 In addition, Box 5 outlines the successful rollout by the Australian government of a nationwide Internet-delivered CBT program. 24 ).…”
Section: What Resources Are Available For Internet-delivered Cbt?mentioning
confidence: 99%
“…41 Patients had unlimited access to the program for 17 weeks. Those in the scheduled therapist support group completed nine scheduled calls with the therapist, whereas those in the requested therapist support group had access to a help line.…”
Section: Box 4: Featured Program -Ocfightermentioning
confidence: 99%
“…Two studies had acceptable quality-one found that a scheduled TMH approach with the system gave better results than use of a requested helpline 46 and the other found that face-to-face treatment was more effective than TMH. 47 Panic Disorder and Phobias. Two studies found preliminary indications of benefit from Internet-based approaches to treatment of panic disorder and social phobia.…”
Section: General Psychiatric and Mental Health Servicesmentioning
confidence: 99%
“…45 Obsessive-Compulsive Disorder. The studies in this group [46][47][48] made use of the computer-aided system BT STEPS, which has an interactive voice response approach. Two studies had acceptable quality-one found that a scheduled TMH approach with the system gave better results than use of a requested helpline 46 and the other found that face-to-face treatment was more effective than TMH.…”
Section: General Psychiatric and Mental Health Servicesmentioning
confidence: 99%
“…For example, the support of a clinician increased the effectiveness of self-help in the treatment of obsessive-compulsive disorder symptoms (Kenwright et al 2005), the guidance of nurses in self-help was an effective way of treating patients with chronic fatigue syndrome (Wearden et al 2006), and physiotherapy combined with self-help was conducive to increasing physical activity in people with multiple sclerosis (Mulligan et al 2013). …”
Section: Effects Of Self-help Support Groups and Assistive Technologymentioning
confidence: 99%